2021
DOI: 10.1002/ajhb.23659
|View full text |Cite
|
Sign up to set email alerts
|

Integrative approaches to dispersing science: A case study of March Mammal Madness

Abstract: Objectives: Public engagement is increasingly viewed as an important pillar of scientific scholarship. For early career and established scholars, navigating the mosaic landscape of public education and science communication, noted for rapid "ecological" succession, can be daunting. Moreover, academics are characterized by diverse skills, motivations, values, positionalities, and temperaments that may differentially incline individuals to particular public translation activities.Methods: Here we briefly context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In this process, we all are learners and knowledge are co-created by promoting critical thinking and reflection (Freire, 2000;Lomeli & Rappaport, 2018) Our colleagues have also shown that the use of social media can be used to reach even wider audiences. March Mammal Madness, a yearly game that teaches about mammal ecology, adaptation, and lifeways currently reaches hundreds of thousands of people and engages educators and their students at all educational levels (Amorim et al, 2021;Hinde et al, 2021) As kids growing up in the Global North, many of us do not learn that observational science or natural history are a possibility in our science classes. Many K-12 students are forced into ideas about experimental science for Science Fairs while organismal focus has largely disappeared from textbooks and high school/college biology curricula (Blumstein & Saylan, 2007;Tewksbury et al, 2014).…”
Section: Conservation Education In Habitat-country Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, we all are learners and knowledge are co-created by promoting critical thinking and reflection (Freire, 2000;Lomeli & Rappaport, 2018) Our colleagues have also shown that the use of social media can be used to reach even wider audiences. March Mammal Madness, a yearly game that teaches about mammal ecology, adaptation, and lifeways currently reaches hundreds of thousands of people and engages educators and their students at all educational levels (Amorim et al, 2021;Hinde et al, 2021) As kids growing up in the Global North, many of us do not learn that observational science or natural history are a possibility in our science classes. Many K-12 students are forced into ideas about experimental science for Science Fairs while organismal focus has largely disappeared from textbooks and high school/college biology curricula (Blumstein & Saylan, 2007;Tewksbury et al, 2014).…”
Section: Conservation Education In Habitat-country Communitiesmentioning
confidence: 99%
“…Our colleagues have also shown that the use of social media can be used to reach even wider audiences. March Mammal Madness, a yearly game that teaches about mammal ecology, adaptation, and lifeways currently reaches hundreds of thousands of people and engages educators and their students at all educational levels (Amorim et al, 2021; Hinde et al, 2021). March Mammals Madness stands out because it has grown over the past ten years and has been effective due to stakeholder partnerships that contribute to and build lesson plans around content.…”
Section: Moving Forwardmentioning
confidence: 99%